Risk management and Insurance - Harrington, Scott E (Mc Graw Hill Education, 2004)
Brief contents: Risk and its Management; Objective of Risk Management; Riks Identification and Diversification of Risk; Insurer Ownership, Financial, and Operational Structure; Insurance Regulation...